2017
DOI: 10.1039/c7nr03717a
|View full text |Cite
|
Sign up to set email alerts
|

Structure-induced variation of thermal conductivity in epoxy resin fibers

Abstract: The ability to control thermal conductivity is important in a wide variety of applications, especially in heat removal, heat insulation, and thermoelectric energy conversion. Herein, we reveal that the thermal conductivity of epoxy resin fibers increases on decreasing the fiber diameter and surpasses the bulk value (0.25 W m K at 300 K) for the fiber with a diameter of 211 nm. The variation of thermal conductivity in epoxy resin fibers can likely be attributed to their microstructure change-enhanced interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…However, Zeng et al . recently reported that a thermal contact resistance accounted for 30% to 50% of the total resistance of an electrospun epoxy resin NF, which was assembled on a suspended microdevice without the aid of electron-beam-assisted metal deposition 23 . Therefore, cyclohexane, which is a non-polar solvent, was dropped on the NFs and the suspended microdevices to reduce the contact thermal resistances between the NFs and the substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Zeng et al . recently reported that a thermal contact resistance accounted for 30% to 50% of the total resistance of an electrospun epoxy resin NF, which was assembled on a suspended microdevice without the aid of electron-beam-assisted metal deposition 23 . Therefore, cyclohexane, which is a non-polar solvent, was dropped on the NFs and the suspended microdevices to reduce the contact thermal resistances between the NFs and the substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Successively, more than 20-fold enhancements of k values were reported for electrospun and rapidly stretched polyethylene NFs 19,20 . In addition to polyethylene NFs, the k values of Nylon-11, polystyrene, and epoxy resin NFs were also significantly higher than those of their bulk counterparts 2123 . This dramatic k increase proposes a possibility that polymer nanofibers can be used for various thermal applications such as thermal interface and functional fabric materials.…”
Section: Introductionmentioning
confidence: 92%
“…Zeng et al [27] measured the thermal conductivity of the epoxy resin fibers made by electrostatic spinning technology and they found the value can be as high as 0.8 Wm -1 K -1 . In their following work [28], they found the thermal conductivity of epoxy resin fibers increases on decreasing the fiber diameter.…”
Section: Introductionmentioning
confidence: 95%
“…Also, it is thought that the degree of crosslinking may be sufficient for gauche conformation, which is formed at a higher temperature, to persist throughout the whole temperature range of the k measurement. As for a diameter dependence of k , several studies reported that the thermal conductivity of an electrospun polymer NF increased with decreasing diameter of the NF due to the effect of molecular chain alignment via electrospinning [6,8,37]. A similar diameter dependence was also observed for the mechanical properties of electrospun polymer NFs [38,39,40,41].…”
Section: Resultsmentioning
confidence: 57%
“…The electrospinning method, which draws nanofibers with an electrostatic force, also enhances the thermal conductivity of nanofibers. There have been several recent studies that reported k enhancement in electrospun Nylon-11, PE, and epoxy nanofibers [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%